Methylmalonic Acid in Amniotic Fluid and Maternal Urine as a Marker for Neural Tube Defects - 罗小平 张炼 魏红 刘皖君 王慕逖 宁琴 (Current medical science, 2004)
To evaluate the implication of methymalonic acid (MMA) in the early diagnosis of neural tube defects (NTD), a quantitative assay for MMA was established by using gas chromatography-mass spectrometry with stable isotope of MMA as an internal standard. Amniotic fluid and maternal urine MMA concentration, maternal serum folate, red blood cell folate and vitamin B12 levels were measured in the middle term of NTD-affected and normal pregnancies. Amniotic fluid and maternal urine MMA concentrations in the middle term of NTD affected pregnancies (1.4±0.9 μmol/L, and 22.1±12.6 nmol/μmol creatinine) were significantly higher than that of normal pregnancies(1.0±0.4μmol/L, and 2.5±1.1 nmol/μmol creatinine). There was no significant difference be-tween normal and NTD pregnancies for serum folate, red blood cell folate and vitamin B12 levels.The results suggested that MMAs in amniotic fluid and maternal urine are sensitive markers for early diagnosis of NTD. Vitamin B12 is an active cofactor involved in the remethylation of homocycteine and its deficiency is an independent risk factor for NTD. MMA is a specific and sensitive marker for intracellular vitamin B12 deficiency. This study suggests that it is necessary to monitor the vitamin B12 deficiency and advocates vitamin B12 supplementation with folate prevention program.